The Impacts of Vocational Rehabilitation - Simen Markussen; Knut Røed (Institute for the Study of Labor (IZA), 2014)
Based on local variations in vocational rehabilitation (VR) priorities, we examine the impacts of alternative VR programs on short- and long-term labor market outcomes for temporary disability insurance (TDI) claimants in Norway. The analysis builds on rich and detailed administrative registers covering 345,000 claimants. We find that a strategy focusing on rapid placement in the regular labor market is superior to alternative strategies giving higher priority to vocational training or sheltered employment. Strategies prioritizing subsidized regular education also tend to be relatively successful in terms of final outcomes, but at the cost of protracted periods of benefit dependency first.
Keywords: C21; C26; H55; I38; J24; 330; treatment effects; social insurance; vocational rehabilitation; program evaluation